2017
DOI: 10.1002/ange.201708271
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Manganese(I) C−H Activation Catalysis in Continuous Flow: Chemoselective Hydroarylation

Abstract: Chemoselective hydroarylations were accomplished by an ovel synergistic Brønsted acid/manganese(I)-catalyzed CÀHa ctivation manifold. Thus,a lkynes bearing O-leaving groups could, for the first time,b ee mployed for CÀH alkenylations without concurrent b-O elimination, thereby setting the stage for versatile late-stage diversifications.A lso described is the first manganese-catalyzed C À Ha ctivation in continuous flow, thus enabling efficient hydroarylations within only 20 minutes. Conflict of interestTheauth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 97 publications
0
5
0
1
Order By: Relevance
“…[54b] Alkynyl cyclic carbonates were also reported as substrates in non-decarboxylative cooperative Brønsted acid/Mn I -catalyzed hydroarylations under continuous flow conditions affording (E)-configured functionalized allylic cyclic carbonates that are useful for latestage diversification. [55] 4. Miscellaneous Heterocyclic Substrates 4.1.…”
Section: Conversion Of Alkynyl-substituted Cyclic Carbonatesmentioning
confidence: 99%
“…[54b] Alkynyl cyclic carbonates were also reported as substrates in non-decarboxylative cooperative Brønsted acid/Mn I -catalyzed hydroarylations under continuous flow conditions affording (E)-configured functionalized allylic cyclic carbonates that are useful for latestage diversification. [55] 4. Miscellaneous Heterocyclic Substrates 4.1.…”
Section: Conversion Of Alkynyl-substituted Cyclic Carbonatesmentioning
confidence: 99%
“…[17] Recently, Ackermann and coworkers have achieved a highly chemo-and regioselective hydroarylation of O-containing propargylic alkynes under synergistic catalysis of Brønsted acid and manganese (Scheme 4). [18] Indoles, thiophenes, pyrroles, tryptophans, and pyridinones were all suitable arene substrates. It was noteworthy that the β-O-elimination process didn't occur at all in the reaction, which was distinguished from previous manganese-catalyzed hydroarylation reactions with β-heteroatom elimination pathways.…”
Section: Olefination Reactions With Alkynesmentioning
confidence: 99%
“…506 The authors demonstrated that the manganese(I)-catalyzed hydroarylation protocol tolerated a wealth of challenging functional groups, such as ester, cyano, halo, and carboxyl (Scheme 92). 509 6.3.2. C−H Activation for Annulation.…”
Section: C−h Addition To C−c Multiple Bondsmentioning
confidence: 99%